2016
DOI: 10.1038/npp.2015.334
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Functional Uncoupling NMDAR NR2A Subunit from PSD-95 in the Prefrontal Cortex: Effects on Behavioral Dysfunction and Parvalbumin Loss after Early-Life Stress

Abstract: In the discussion section of this paper, on page 2673, left column, second paragraph, the second sentence should read 'Although developmental influences of NR2A specifically within the PFC have not been widely examined, NMDAR in the PFC have been shown to shift from NR2B-mediated EPSPs toward more NR2A-mediated EPSP during the early-pre-adolescent period (P20-P30; Wang and Gao, 2009).' Neuropsychopharmacology (2016Neuropsychopharmacology ( ) 41, 1188

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The reduction in PV + cellular density, observed in PrL is in line with the results of studies that employed a 3 h daily separation protocol during the first three postnatal weeks (Leussis et al, 2012;Ganguly et al, 2016;Grassi-Oliveira et al, 2016), as well as a previous result from our laboratory (Aksic et al, 2021). In another study, Helmeke et al (2008) reported an increase in the number of PV + neurons in the dorsal medial PFC of an adult Octogon degus which appeared strikingly opposite to our findings (Helmeke et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The reduction in PV + cellular density, observed in PrL is in line with the results of studies that employed a 3 h daily separation protocol during the first three postnatal weeks (Leussis et al, 2012;Ganguly et al, 2016;Grassi-Oliveira et al, 2016), as well as a previous result from our laboratory (Aksic et al, 2021). In another study, Helmeke et al (2008) reported an increase in the number of PV + neurons in the dorsal medial PFC of an adult Octogon degus which appeared strikingly opposite to our findings (Helmeke et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…While the effects of ES on cognition have been extensively studied in adult animals in our own and other research groups [4,52], it is worth highlighting that several recent studies have started to examine this issue in adolescent rodents. Studies with maternal separation or deprivation models reported that ES impaired spatial learning and memory in morris water maze test [38], novel object recognition memory [53], and temporary order memory [54] in adolescent rodents. To our knowledge, only one study has used the LBN paradigm and found that exposure to LBN during PND4-11 led to spatial object recognition memory loss in adolescent male mice [7].…”
Section: Discussionmentioning
confidence: 99%